2007
DOI: 10.1002/macp.200600392
|View full text |Cite
|
Sign up to set email alerts
|

Micellization of PS‐PMMA Diblock Copolymers in an Ionic Liquid

Abstract: Three polystyrene‐block‐poly(methyl methacrylate) (PS‐PMMA) block copolymers with varying molecular content have been shown to form micelles when dissolved in the ionic liquid 1‐butyl‐3‐methylimidazolium hexafluorophosphate (BMIM PF6). The micellar structure was studied via cryogenic transmission electron microscopy and dynamic light scattering, and a morphological transition from spherical to cylindrical micelles was observed upon reduction of the PMMA volume fraction. The possibility of frozen micellar morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 32 publications
6
68
0
Order By: Relevance
“…Accordingly, the temperature responsiveness was also examined in three different solvent composition regions: the water content (WC) from 0.025 to 0.037 (I), WC from 0.037 to 0.049 (II), and WC above 0.049 (III). Although the micellizaiton behaviors of St/MMA block copolymer have been studied in few systems previously, a block copolymer with similar molecular weight and the same composition was used as control experiments to get more insight into the temperature responsiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the temperature responsiveness was also examined in three different solvent composition regions: the water content (WC) from 0.025 to 0.037 (I), WC from 0.037 to 0.049 (II), and WC above 0.049 (III). Although the micellizaiton behaviors of St/MMA block copolymer have been studied in few systems previously, a block copolymer with similar molecular weight and the same composition was used as control experiments to get more insight into the temperature responsiveness.…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45] More recently, there have been reports on more concentrated systems where it has been demonstrated that blending ILs with BCPs such as PS-b-poly(2-vinyl pyridine), [46][47][48] PS-b-poly (ethylene oxide) 49 [PEO], and PEO-b-poly(propylene oxide)-b-PEO 50 can lead to changes in morphology and d-spacing of the phase-separated domains. In this study, we blend 1-ethyl-3-methylimidazolium …”
Section: Introductionmentioning
confidence: 99%
“…They also found that three polystyrene-block-poly(methyl methacrylate) (PS-PMMA) block copolymers with varying molecular content have been shown to form micelles when dissolved in bmimPF 6 . A morphological transition from spherical to cylindrical micelles was observed upon reduction of the PMMA volume fraction [29]. The transfer of aggregation structure by changing the surfactant molecular parameters or system variable such as concentration and temperature has been realized in traditional solvents [1].…”
Section: Self-assembled Micelles In Ilsmentioning
confidence: 99%